SINGLE PARENTING AND THE CONSTRUCTION OF SAKINAH FAMILIES: INTEGRATING ISLAMIC FAMILY LAW AND ROLE STRAIN THEORY - Siti Nafilatul Ahlamiyah; Mujiburrohman Mujiburrohman (JURNAL HAKAM, 2026)
This study examines the challenges of single parenting in realizing a sakinah family from the perspectives of Islamic family law and Role Strain Theory. The increasing prevalence of single-parent households has raised concerns regarding the sustainability of family harmony and parental responsibilities, while existing studies tend to separate normative Islamic teachings from sociological analysis. This study aims to analyze the relevance of Qur'an Surah An-Nisa verse 9 in guiding parental responsibilities and to explain the role strain experienced by single parents in maintaining family stability. Employing a qualitative library research approach, the study analyzes Qur'anic exegesis, scholarly literature, and sociological theories related to family dynamics and parenting. The findings indicate that single parents experience multiple role demands as economic providers, caregivers, educators, and emotional supporters, resulting in role strain. However, these pressures do not necessarily undermine family harmony, as adaptive coping strategies, religious values, and social support can strengthen parental resilience. Qur'an Surah An-Nisa verse 9 provides a normative framework emphasizing the protection of future generations through responsibility, compassion, and moral commitment. The study further demonstrates that the realization of a sakinah family depends more on the quality of parenting and value internalization than on the completeness of family structure. The novelty of this research lies in integrating Islamic family law with Role Strain Theory to provide a comprehensive framework for understanding single parenting in contemporary Muslim societies. The findings contribute to the development of Islamic family law and family sociology while offering practical insights for strengthening family resilience through religious and social support systems.